Performance evaluation of BladeRF and HackRF SDRs in security tests for GPS systems - Marçal, Vitor; Ferrão, Isadora Garcia; Allão, Daniel; Silva, Lucas Gonzalez Da; Castelo Branco, Kalinka (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
With the increasing popularity of unmanned aerial vehicles (UAVs), their security is becoming increasingly critical, especially given the rising incidence of unauthorized global positioning system (GPS) attacks, which are the most common in UAVs and particularly difficult to detect. In this context, it is crucial to develop and implement effective measures to protect UAVs against these attacks, which not only compromise the safety of aerial operations but also pose potential threats to privacy, national security, and the integrity of satellite navigation systems. This study compares two popular software-defined radio (SDR) platforms, BladeRF and HackRF, exploring their applicability and performance through a systematic comparison in a controlled GPS attack scenario using a real UAV.